Selection strategies of segregant soybean populations for resistance to Asian rust - Ribeiro, Aliny Simony; Toledo, José Francisco Ferraz de; Ramalho, Magno Antonio Patto (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to identify the for the more promising parental combinations to obtain lines with good resistance to soybean Asian rust (Phakopsora pachyrhizi). Two experiments were carried out in the field during the 2006/2007 and 2007/2008 growing seasons, to determine the percentage of infected leaf area of individual plants of five parents and their segregant F2 and F3 populations. The data obtained indicates that additive genetic variance predominates in the control of soybean resistance to Asian rust, and that the year and time of assessment do not significantly influence the estimates of the genetic parameters obtained. The narrow-sense heritability (h2r) ranged from 23.12 to 55.83%, and indicates the possibility of successful selection of resistant individuals in the early generations of the breeding program. All the procedures used to select the most promising populations to generate superior inbred lines for resistance to P. pachyrhizi presented similar results and identified the BR01-18437 x BRS 232 population as the best for inbred line selection.
Keywords: Glycine max; Phakopsora pachyrhizi; additive variance; heritability; selection